VALUASI HARGA SAHAM PERDANA PT. BINTRACO DHARMA TBK - Tarsimin Tarsimin; Cepi Pahlevi; Muhammad Sobarsyah (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
Valuation of initial share price must be undertaken by companies that conduct an initial public offering (IPO). This study aims to assess the initial stock price made by PT. Bintraco Dharma, Tbk a car sales and finance company. The design of this study uses data proposed sampling collected by researchers from various sources such as company websites, automotive related agencies and departments as well as website provider financial reports and stock prices on the Indonesia Stock Exchange. The result of research with three valuation methods used by the researcher shows that the initial share offering of PT. Bintraco Dharma, Tbk for Rp 1,750, - is undervalued because each method produces valuation value above the offering price ie discounted free cash flow to the firm stock price Rp 1.967, -, the relative valuation method with the average price to earnings ratio industry based on 10 automotive companies in BEI Rp 2.472, - and method of price to earnings ratio with multivariate regression analysis resulted in price Rp 2.084,. Multivariate analysis showed that return on asset (P = 0.0081 <0.5%) had a significant influence on price to earnings ratio while the other four variable such as dividend payout ratio, cost of debt, debt to equity ratio, and risk (beta) earnings ratio for shares of PT. Bintraco Dhama, Tbk is less significant. The result of determination test shows the value of R-square = 0.1603 or about 16.03% stock price is determined by the independent variable used in the research and the rest (83.97%) is determined by other factors, so that the next researchers can do the valuation by using variables other than used in this research. It was concluded that PT. Bintraco Dharma, Tbk is offered undervalued based on valuation using three methods used in this research, so that investors should buy and hold within a certain period until the price approaches its intrinsic value considering the good fundamentals of the company several years.